AVAILABILITY OF LEGISLATION REGULATIONS IN PROVIDING LEGAL PROTECTION OF LAND WITH CUSTOM RIGHTS OF CUSTOMARY COMMUNITIES IN INDONESIA: KETERSEDIAAN PERATURAN PERUNDANG-UNDANGAN DALAM MEMBERIKAN PERLINDUNGAN HUKUM ATAS TANAH HAK ADAT MASYARAKAT ADAT DI INDONESIA - Lubis, Asmadi (UPMI Proceeding Series, 2023)
During this period of accelerated development, there were many problems with the existence of indigenous peoples and their rights. these problems place the position of indigenous peoples at a weak and marginalized level. because there is an imbalance in the meaning of all parties involved in positioning customary land and customary law communities. the problem discussed in this paper is how the availability of legal regulations in providing legal protection of land with customary rights in indonesia. availability of regulations and laws for progressive legal protection for the existence of indigenous and tribal peoples in realizing their welfare. The method used in this research is normative juridical. the results of this study the availability of laws and regulations in Indonesia has guaranteed legal protection for indigenous and tribal peoples in Indonesia and if we look based on legal pluralism and the legal system in Indonesia.